Enterprise Information Systems VI - Seruca, Isabel; Cordeiro, José; Hammoudi, Slimane; Filipe, Joaquim (Springer Netherlands : Imprint: Springer, 2006)
This book contains the best papers of the Sixth International Conference on Enterprise Information Systems (ICEIS 2004), held in Porto (Portugal) and organized by INSTICC (Institute for Systems and Technologies of Information, Communication and Control) in collaboration with PORTUCALENSE UNIVERSITY, who hosted the event. Following the route started in 1999, ICEIS has become a major point of contact between research scientists, engineers and practitioners on the area of business applications of information systems. This conference has received an increased interest every year, from especially from the international academic community, and it is now one of the world largest conferences in its area. This year, five simultaneous tracks were held, covering different aspects related to enterprise computing, including: "Databases and Information Systems Integration", "Artificial Intelligence and Decision Support Systems", "Information Systems Analysis and Specification", "Software Agents and Internet Computing" and "Human-Computer Interaction". The sections of this book reflect the conference tracks.